Mining the transcriptomes of four commercially important shellfish species for single nucleotide polymorphisms within biomineralization genes - Vendrami, David; Shah, Abhijeet; Telesca, Luca; Hoffman, Joseph (Marine Genomics, 2016)
Vendrami D, Shah A, Telesca L, Hoffman J. Mining the transcriptomes of four commercially important shellfish species for single nucleotide polymorphisms within biomineralization genes. MARINE GENOMICS . 2016;27:17-23. Transcriptional profiling not only provides insights into patterns of gene expression, but also generates sequences that can be mined for molecular markers, which in turn can be used for population genetic studies. As part of a large-scale effort to better understand how commercially important European shellfish species may respond to ocean acidification, we therefore mined the transcriptomes of four species (the Pacific oyster Crassostrea gigas, the blue mussel Mytilus edulis, the great scallop Pecten maximus and the blunt gaper Mya truncata) for single nucleotide polymorphisms (SNPs). Illumina data for C. gigas, M. edulis and P. maximus and 454 data for M. truncata were interrogated using GATK and SWAP454 respectively to identify between 8267 and 47,159 high quality SNPs per species (total = 121,053 SNPs residing within 34,716 different contigs). We then annotated the-transcripts containing SNPs to reveal homology to diverse genes. Finally, as oceanic pH affects the ability of organisms to incorporate calcium carbonate, we honed in on genes implicated in the biomineralization process to identify a total of 1899 SNPs in 157 genes. These provide good candidates for biomarkers with which to study patterns of selection in natural or experimental populations. (C) 2016 Elsevier B.V. All rights reserved.